Practical Google Analytics and Google Tag Manager for Developers - Weber, Jonathan; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2015)
Whether you’re a marketer with development skills or a full-on web developer/analyst, Practical Google Analytics and Google Tag Manager for Developers shows you how to implement Google Analytics using Google Tag Manager to jumpstart your web analytics measurement. Whether you're starting from scratch on a new website or working to re-engineer or enhance a Google Analytics account you have inherited, this book provides the tools. There’s a reason that so many organizations use Google Analytics. Effective collection of web analytics data through Google Analytics can reduce customer acquisition costs, turn visitors into customers, provide priceless feedback on new product initiatives, and offer insights that will grow a customer or client base. So where does Google Tag Manager fit in? With a growing list of features and rapid adoption across industries, Google Tag Manager allows for unprecedented collaboration between marketing and technical teams, lightning fast updates to your site, and standardization of the most common tags for on-site tracking and marketing efforts. As Practical Google Analytics and Google Tag Manager for Developers shows, to achieve the rich data you're really after to better serve your users' needs, you'll need the tools Google Tag Manager provides for a best-in-class implementation of Google Analytics measurement on your site. Written by data evangelist and Google Analytics expert Jonathan Weber and the team at LunaMetrics, this book offers foundational knowledge, a collection of practical Google Tag Manager recipes, well-tested best practices, and troubleshooting tips to get your implementation in tip-top condition. It covers topics including: • Google Analytics implementation via Google Tag Manager • How to customize Google Analytics for your unique situation • Using Google Tag Manager to track and analyze interactions across multiple devices and touch points • How to extract data from Google Analytics and use Google BigQuery to analyze Big Data questions .
Part I Implementing Google Analytics with Google Tag Manager -- Chapter 1 Google Analytics Fundamentals -- Chapter 2 Basic Google Analytics Measurement -- Chapter 3 Introducing Google Tag Manager (GTM) -- Chapter 4 Testing Your Implementation -- Part II Enhancing Website Data with Google Tag Manager -- Chapter 5 Tracking Interactions Using Google Tag Manager -- Chapter 6 Goals: Measuring Conversions -- Chapter 7 ECommerce: Tracking Products and Purchases -- Chapter 8 Cleaning Up and Enriching Data with GA and GTM -- Chapter 9 Measuring Campaigns and Troubleshooting Traffic Sources -- Chapter 10 Tracking Users across Devices -- Chapter 11 Providing Additional Data about Your Users -- Part III Collecting Data from Other Sources -- Chapter 12 GA’s Measurement Protocol: Collecting Data from Anywhere -- Chapter 13 Collecting Data from Mobile Apps with GA and GTM -- Chapter 14 Importing Data into GA -- Chapter 15 Using GA with BigQuery for Big Data Analysis -- Appendix Google Analytics and Google Tag Manager APIs. .
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems